Potential Benefits of Laparoscopic Repair of Duodenal Atresia: Insights from a Retrospective Comparative Study - Sidler, Martin; Djendov, Florin; Curry, Joe I.; Blackburn, Simon; Giuliani, Stefano; Eaton, Simon; Mullassery, Dhanya; Cross, Kate M.; De Coppi, Paolo (European Journal of Pediatric Surgery, 2020)
Introduction Congenital duodenal obstruction (CDO) repair can be performed open or laparoscopically. We aimed to determine the potential benefit of laparoscopic repair regarding tolerance of enteral feeding, postoperative pain, hospital stay, and complication rate.Materials and Methods In a single-center retrospective cohort study, we compared neonates with isolated CDO operated open versus laparoscopically from 2010 to 2019. No transanastomotic tubes were used, and anastomoses were created in a side-to-side fashion in all cases. An early feeding policy is applied for all cases operated at our institution. Statistical comparison was performed using the Mann–Whitney's test or Fisher's exact test where appropriate.Results Forty-one patients analyzed were similar regarding body weight, gestational age, and proportion of patients with trisomy 21. Median follow-up was 21 months. Four (20%) out of 20 laparoscopic procedures started laparoscopically were converted to open. Comparing the 21 open with the 16 laparoscopically completed patients, median anesthetic duration was shorter by 18% in the open versus laparoscopic completed group (218 vs. 179 minutes, respectively; p = 0.025). Median postoperative time to full enteral feeds was shorter by 4 days in the first group (7 vs. 11 days, respectively; p = 0.028). In accordance, the median duration of parenteral nutrition (PN) was less than half in the laparoscopic completed compared with the open group (5 vs. 11.5 days, respectively; p = 0.031). Postoperative opioids were required for only half the duration in the laparoscopically completed group compared with open (2 vs. 4 days, respectively; p = 0.026). Outcomes such as length of stay, the occurrence of strictures or adhesions requiring reintervention, or line sepsis were similar in both groups.Conclusion Patients undergoing laparoscopic CDO repair at our institution benefited from shorter time to full enteral feeds, and reduced the need for PN as well as postoperative pain medication.
Keywords: neonatal; surgery; duodenal atresia; laparoscopy; minimally invasive surgery